Contribution of Ref(2)p to regulation of Drosophila notum epithelial cell apico-basal polarity and phenotype - Shohayeb, Belal; Georgiou, Marios; Layfield, Robert (2015)
Cell polarity impacts on the maintenance of cell shape, cell-cell junction integrity, and protrusion formation and dynamics. Further, polarity additionally regulates cell movement, proliferation and differentiation. Conversely when cells lose their polarity they may be susceptible to dysfunction that may underlie degenerative disorders. Cell polarity and polarity protein complexes are highly conserved between different organisms from unicellular to multi-cellular, and from invertebrates to vertebrates. The focus of this study is the apico-basal polarity that is established normally in epithelial cells.